A new species of genus Agryllus Gorochov, 1994 from Yunnan, China (Orthoptera: Gryllidae: Gryllinae) - Xu, Yue; Gao, Xue-Di; Liu, Yun-Fei; He, Zhu-Qing (Zootaxa, 2018)
One new species, Agryllus apterus He sp. nov., is described from Yunnan, China. This new species is wingless, which is different from all other Agryllus species. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).